Towards the Use of LITMUS RT as a Testbed for Multiprocessor Scheduling in Energy Harvesting Real-Time Systems - Borin, Lais; Castro, Márcio; Plentz, Patricia Della Méa (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2017: Anais do VII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2017)
Energy reduction is a key issue for the design of real-time embedded systems. In this context, energy harvesting has emerged as a feasible option to increase the autonomy of battery-based real-time embedded systems and became subject of intensive research. However, current studies usually rely on discrete driven in-house simulators or use mathematical models only. Unfortunately, those approaches hide several important aspects of real-time embedded systems, resulting in non-realistic and incomplete analyses. Moreover, they are not publicly available to the research community, making it difficult to reproduce results. In this paper we propose to use LITMUS-RT, an open-source real-time extension of the Linux kernel with a focus on multiprocessor real-time scheduling and synchronization, as an experimental platform for energy harvesting real-time systems research. Our results show that the proposed proof-of-concept solution implemented with LITMUS-RT allows researchers to study the behavior of real-time schedulers in the context of an energy harvesting real-time system, and could be integrated in the LITMUS RT kernel in the future.